Physics of the impossible : a scientific exploration of the world of phasers, force fields, teleportation and time travel - Kaku, Michio (London : Penguin, 2009)
Shows how our most far fetched ideas today are destined to become tomorrow's reality. This books looks at the science of the future and explains what's just around the corner, what we might have to wait a few millennia to get our hands on and how surprisingly little of it is truly impossible.
First published: 2008.
Includes bibliographical references and index.
Keywords: Human-machine systems; Mathematical physics; Physics in literature; Physics -- Miscellanea; Science -- Miscellanea